PENGARUH VARIASI SPRAY RAILS PADA MODEL LAMBUNG WAVE-PIERCING BOW TERHADAP FAKTOR KOMPONEN HAMBATAN KAPAL - Ananta Farhan Aulia (2021)
On high speed vessel, various modifications can be made to optimize the hull itself, such as the use of spray rails. The function of these spray rails is to increase the lift on the ship with a planing hull. This study aims to compare the bare hull model and the hull with spray rails at various positions of the spray rails. This study uses a gastric model from the experiment of Jeonghwa Seo et al., (2016). Modeling of the hull and spray rails using the maxsurf modeler and analysis of ship resistance using ansys Fluent. Based on the simulation results, the model with 24% T spray rails has a lower total resistance of 1% compared to the bare hull hull model. Meanwhile, in the 8% T spray rails model, the total resistance value is 1% greater than the bare hull model. So that the results obtained from the study that the addition of spray rails can be beneficial or provide a dis-advantage to ship resistance.